LINGUISTIC ANALYSIS OF NECESSITY EXPRESSIONS IN FINNISH AND POLISH LEGAL TEXT IN TERMS OF DEONTIC STRENGTH - RYDZEWSKA-SIEMIĄTKOWSKA, Joanna (Comparative Legilinguistics, 2016)
The aim of this article is to highlight an issue of expressing deontic modality in Finnish and Polish in a legal context in terms of deontic strength. The particular interest is put on the Finnish necessive expression on –t(t)ava and its Polish equivalents. The choice of this expression is motivated by the fact that it is the most frequent deontic expression that occurred in the analysed material. It is argued that although the meaning of the Finnish and English modal expressions are almost parallel, the corresponding Polish expressions show some discrepancy. This paper aims at giving insight into the differences of the phenomenon on the basis of the Treaty on Functioning of the European Union.